Influence of Plant Fraction, Soil, and Plant Species on Microbiota: a Multikingdom Comparison - Andrzej Tkacz (American Society for Microbiology, 2020)
ABSTRACT Plant roots influence the soil microbiota via physical interaction, secretion, and plant immunity. However, it is unclear whether the root fraction or soil is more important in determining the structure of the prokaryotic or eukaryotic community and whether this varies between plant species. Furthermore, the leaf (phyllosphere) and root microbiotas have a large overlap; however, it is unclear whether this results from colonization of the phyllosphere by the root microbiota. Soil, rhizosphere, rhizoplane, and root endosphere prokaryote-, eukaryote-, and fungus-specific microbiotas of four plant species were analyzed with high-throughput sequencing. The strengths of factors controlling microbiota structure were determined using permutational multivariate analysis of variance (PERMANOVA) statistics. The origin of the phyllosphere microbiota was investigated using a soil swap experiment. Global microbial kingdom analysis conducted simultaneously on multiple plants shows that cereals, legumes, and Brassicaceae establish similar prokaryotic and similar eukaryotic communities inside and on the root surface. While the bacterial microbiota is recruited from the surrounding soil, its profile is influenced by the root itself more so than by soil or plant species. However, in contrast, the fungal microbiota is most strongly influenced by soil. This was observed in two different soils and for all plant species examined. Microbiota structure is established within 2 weeks of plant growth in soil and remains stable thereafter. A reciprocal soil swap experiment shows that the phyllosphere is colonized from the soil in which the plant is grown. IMPORTANCE Global microbial kingdom analysis conducted simultaneously on multiple plants shows that cereals, legumes, and Brassicaceae establish similar prokaryotic and similar eukaryotic communities inside and on the root surface. While the bacterial microbiota is recruited from the surrounding soil, its profile is influenced by the root fraction more so than by soil or plant species. However, in contrast, the fungal microbiota is most strongly influenced by soil. This was observed in two different soils and for all plant species examined, indicating conserved adaptation of microbial communities to plants. Microbiota structure is established within 2 weeks of plant growth in soil and remains stable thereafter. We observed a remarkable similarity in the structure of a plant’s phyllosphere and root microbiotas and show by reciprocal soil swap experiments that both fractions are colonized from the soil in which the plant is grown. Thus, the phyllosphere is continuously colonized by the soil microbiota.